On the basis of sex [videorecording (DVD)] - Jones, Felicity; Hammer, Armie, 1986-; Theroux, Justin; Waterston, Sam; Bates, Kathy, 1948- (Universal Pictures Home Entertainment, 2019)
The film tells an inspiring and spirited true story that follows young lawyer Ruth Bader Ginsburg as she teams with her husband Marty to bring a groundbreaking case before the US Court of Appeals and overturn a century of gender discrimination. The feature will premiere in 2018 in line with Justice Ginsburg's 25th anniversary on the Supreme Court.